Perspective on Sub-national Governance of Crossborder Regions: Democratic Governance in Anti-democratic Times? - Svensson, Sara (Frontiers in Political Science, 2021)
In the past decades, subnational cooperation between municipalities and regions has become more common all over the world. In Europe and its neighborhood this tendency has been especially visible, much due to policy advocacy and technical assistance by regional intergovernmental organizations such as the Council of Europe, the European Union and the Organization for Security and Cooperation in Europe. This development accelerated in the 1990s in tandem with the transition and democratization processes that started after the fall of the Soviet Union. However, in many places democratization has stopped or started to reverse, leading to backsliding away from democracy. While democracy as always been different in crossborder regions due to the special status of their governance arrangements, this new development accentuates a need for new tools to understand the implications of various threats to democracy for the future of crossborder cooperation. This Perspective article provides an overview of the literature on participatory governance and democracy with relation to border regions, and suggests some mechanisms whereby current backsliding developments might harm sub-national cross-border democracy and a way by which current indexes of democracy at the national level could be adapted to the ‘messy’ spaces of cross-border regional governance. This allows the Perspective article to be useful to both further research in the area and policy practitioners. Empirical examples from Central and Eastern Europe, within and outside the European Union, will be used as illustrations.